2009
DOI: 10.4103/0253-7184.55476
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treatment: The single biggest obstacle to HIV/AIDS treatment adherence in lower-middle class patients in Mumbai, India

Abstract: Background:This study analyzes the social, economic and behavioral factors most frequently associated with adherence to Highly Active Antiretroviral Treatment (HAART) in urban India.Materials and Methods:Data was collected in a metropolitan teaching hospital in Mumbai using a cross-sectional survey design. Face-to-face interviews were conducted with 152 patients. The semistructured survey included both open and closed ended questions on socio-demographic, economic and behavioral factors. Factors affecting trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…There were seven cross-sectional studies(11122122232425) and one retrospective chart analyses. (26) Three studies were conducted in southern India(212426) and two each in western(1225) and north India. (2223) One study enrolled participants from western and northern India.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were seven cross-sectional studies(11122122232425) and one retrospective chart analyses. (26) Three studies were conducted in southern India(212426) and two each in western(1225) and north India. (2223) One study enrolled participants from western and northern India.…”
Section: Resultsmentioning
confidence: 99%
“…showed a rate of 57%. (12) Therefore, the aim of this study is to systematically assess the rate of ART adherence across all studies conducted in India and the reasons for non-adherence (if any). We have performed a systematic review and metaanalysis to provide conclusive data on ART adherence in HIV/AIDS patients in India.…”
Section: Introductionmentioning
confidence: 99%
“…The current evidence has primarily centered on HIV-infected adults, and suggests several mechanisms for why this may be the case. HIV-infected individuals may have inadequate economic access to ART, limiting resources to pay for real or perceived costs related to medications and treatment, including travel costs to remain engaged in care [1517]. Many individuals living with HIV, including families affected by AIDS, may have lost employment or other sources of income over the course of their illness.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly cART adherence studies by Kumarasamy et al , Naik et al and Wanchu et al conducted in India also showed the association of high cost of cART as a barrier to cART adherence. [91213] However, patients taking cART from private practitioners generally still find cost as a major barrier for cART. One study by Sarna et al .…”
Section: Discussionmentioning
confidence: 99%